MSME Development and Assistance Through Business Digitalization for Pawon Enak MSMEs in Medokan Ayu Village: Pengembangan Dan Pendampingan UMKM Melalui Digitalisasi Usaha Untuk UMKM Pawon Enak di Kelurahan Medokan Ayu - Althafa A. Mu'min; Rusdi Hidayat Nugroho (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
This article is a form of community service through the KKN-T program which aims to help develop Pawon Enak MSMEs in Medokan Ayu Village, Rungkut District, Surabaya City. The problem that exists is a lack of understanding regarding the use and utilization of digital marketing. The method used is problem identification, digital marketing assistance, and a product rebranding process. The activities took the form of creating social media and a new logo for UMKM Pawon Enak. It is hoped that the results of the community service program for developing MSMEs through business digitalization can make businesses better and develop.